Dialektika dalam Reformulasi Kriteria Rukyatul Hilal: Dari Rukyat Mutlak hingga QRNU - Hijriyati, Muthi'ah; Lusdiyanto, Karis (Faculty of Shariah UIN Ponorogo, 2024)
Nahdlatul Ulama' as a representative of a community organization that views rukyah as the basis for determining the start of the month is often faced with hisab. However, history records that the NU’s ijtihad process moved dynamically and did not reject hisab. Starting from using rukyah absolutely, then hisab is used as a